Frontal lobe metabolic alterations in autism spectrum disorder: a 1H-magnetic resonance spectroscopy study - Margari L (Dove Medical Press, 2018)
Lucia Margari,1 Andrea De Giacomo,1 Francesco Craig,2 Roberto Palumbi,1 Antonia Peschechera,1 Mariella Margari,1 Francesca Picardi,3 Marina Caldarola,3 Marilena Anna Maghenzani,4 Franca Dicuonzo3 1Department of Basic Medical Sciences, Neuroscience and Sense Organs, Child Neuropsychiatry Unit, University of Bari Aldo Moro, Azienda Ospedaliero Universitaria Consorziale Policlinico di Bari, Bari, Italy; 2Scientific Institute, IRCCS E. Medea, Unit for Severe Disabilities in Developmental Age and Young Adults, Developmental Neurology and Neurorehabilitation, Brindisi, Italy; 3Department of Basic Medical Sciences, Neuroscience and Sense Organs, Neuroradiology Unit, University of Bari Aldo Moro, Azienda Ospedaliero Universitaria Consorziale Policlinico di Bari, Bari, Italy; 4Emergency Department, Anesthesia and Intensive Care Unit, University of Bari Aldo Moro, Azienda Ospedaliero-Universitaria Policlinico di Bari, Bari, Italy Purpose: Recently, neuroimaging studies were performed using 1H-magnetic resonance spectroscopy (1H-MRS), revealing a quantitative alteration of neurochemicals (such as neurotransmitters and metabolites) in several brain regions of patients with autism spectrum disorder (ASD). The involvement of the frontal lobe in the neurobiology of ASD has long been documented in the literature. Therefore, the aim of this study was to analyze the alterations of N-acetylaspartate/creatine (NAA/Cr) and choline/Cr (Cho/Cr) ratios in the frontal lobe subcortical white matter (WM) in ASD patients, in order to reveal any alteration of metabolites that might be the expression of specific clinical features of the disorder.Patients and methods: An 1H-MRS study of the frontal lobe subcortical WM was performed in 75 children with ASD and in 50 age-matched controls to evaluate the functional activity of this brain region.Results: NAA/Cr and Cho/Cr ratios were significantly altered in ASD, compared to control subjects. Moreover, in the ASD group, NAA/Cr was significantly lower in patients with a cognitive impairment.Conclusion: Results from this study confirm the existence of brain metabolites’ alterations in frontal lobe WM in children with ASD, supporting the relevance of this brain region in the clinical expressions of this disorder, including its role in the cognitive impairment. Further 1H-MRS investigations will allow to comprehensively explain the relationship between metabolic alteration in a specific brain region and specific clinical features of ASD. Keywords: autism, neurodevelopmental disorder, cognitive impairment, neuroimaging, brain metabolites